Factors influencing attitude towards change among academic staffs of UiTM Melaka / Muhammad Nazmie Othmam - Othmam, Muhammad Nazmie (Faculty of Business and Management, 2014)
This research focused on attitude towards change between organizational commitment and occupational stress. It seeks to understand the factors influencing attitude towards change among academic staffs of UiTM Melaka. The methodology that used in this research is a quantitative from a data survey throughout a questionnaire. The data was randomly collected from 50 respondent among academic staffs at UiTM Melaka. The population of academic staffs at UiTM Melaka was around 350 and the sampling size use just 50 respondent. In order to get analysis data, researcher use data collection method and Statistical Package for Social Science 20 (SPSS) data analysis method. The major finding in this research is there is a relationship between occupational stress and attitude towards change. The recommendation for future research are it should involve all staff at UiTM Melaka and researcher should use the specific data collection method.